THE SOCIAL STATUS OF HAJJ IN RURAL LAMPUNG - Lestari, Amilia; Kamaludin, Mohamad Imam; Wijayanto, Fery (Institut Agama Islam Negeri Metro, 2024)
This study examines the impact of performing the Hajj pilgrimage on an individual's social status in rural Lampung communities. The aim of this research is to analyze how the titles 'Haji' or 'Hajjah' influence social standing, religious leadership roles, and their relation to economic capacity. The research methods used are observation and interviews. The findings show that individuals who have completed the Hajj experience a significant rise in social status. The title